The construction and analysis of M13 libraries prepared from YAC DNA. - Vaudin, M (1995)
Yeast artificial chromosomes (YACs) provide a powerful way to isolate and map large regions of genomic DNA and their use in genome analysis is now extensive. We modified a series of procedures to produce high quality shotgun libraries from small amounts of YAC DNA. Clones from several different libraries have been sequenced and analyzed for distribution, sequence integrity and degree of contamination from yeast DNA. We describe these procedures and analyses and show that sequencing at about 1-fold coverage, followed by database comparison (survey sequencing) offers a relatively quick method to determine the nature of previously uncharacterized cosmid or YAC clones.